Results of bridging LCP along with corticocancellous autogenous bone graft and calcium hydroxyapatite blocks in gap nonunion of long bones - Agarwal, Ankur (International Journal of Research in Orthopaedics, 2018)
Background: High-energy trauma is an important cause of compound fractures of long bones that in turn results into bone gap due to bone loss or high communition with resultant displacement of minute fracture fragments and hence non-union. Bone resorption or surgical excision for infection or tumour also leads to gap non-unions. Methods: Forty-one patients having fracture of long bones of extremities with a bone gap of upto 2 inches were enrolled and were treated with autogenous bone grafting and calcium hydroxyapatite (CHA) blocks along with fixation by a locked compression plate (LCP) and plaster slab. The average follow-up period was ten months. One patient was excluded from the study due to drop out from follow up. Results: In 23 (57.5%) patient’s radiological union occurred by 24-26 weeks. In 16 (40%) patients, radiological union was seen between 26-28 weeks, while in one (2.5%) patient union was seen at 30 weeks. Also, it was seen that smaller the length of gap, the faster was the union. Excellent results were seen in the majority of 25 patients (62.5%), good results in 11 patients (27.5%), fair results in 3 patients (7.5%) and poor outcome in 1 patient (2.5%). Also, it was seen that smaller the gap size, better was the outcome. Conclusions: The technique of bridge plating using internal fixator i.e. LCP along with autogenous corticocancellous bone graft and CHA blocks is a fairly good technique to treat gap non unions. It has its own advantages of avoiding complications associated with large external frame constructs. However, larger gap size limits the usefulness of this technique.